PENGARUH LIKUIDITAS, LEVERAGE, DAN PROFITABILITAS TERHADAP FINANCIAL DISTRESS PERUSAHAAN MAKANAN DAN MINUMAN: Pengaruh Likuiditas, Leverage, dan Profitabilitas Terhadap Financial Distress Perusahaan Makanan dan Minuman - Fildzah, Natasya Choirin Nur; Rachmawati, Anisa (Jurnal Ilmiah Akuntansi dan Finansial Indonesia, 2025)
This study aims to examine the effect of liquidity, leverage, and profitability on financial distress in food and beverage sub-sector manufacturing companies listed on the IDX in 2021-2023. This study uses the Altman Z-Score model to measure the condition of companies heading towards bankruptcy. The data used in this study are secondary data from the company's annual report. The sampling technique in this study used the purposive sampling method with a population of 69 companies and a final sample of 185 data. The data analysis technique in this study used the logistic regression analysis method. The results of the study indicate that liquidity proxied by the current ratio has a negative effect and the quick ratio has a positive effect on financial distress, the leverage variable proxied by the debt to asset ratio has a positive effect on financial distress while the debt to equity ratio does not have a positive effect on financial distress, and the profitability variable proxied by return on assets has a negative effect on financial distress while return on equity does not have a negative effect on financial distress.